THERMALLY MODIFIED WOOD: TECHNOLOGIES, TRENDS AND PROSPECTS - Maksymiv, Volodymyr; Andrashek, Yosyp; Shchupakivskyy, Roman (Forestry, Forest, Paper and Woodworking Industry, 2024)
Because of the original properties thermally modified wood found widespread use and market dynamic of consumption. The technologies, usually created by the method of "trial and error" and not perfect. To develop effective modes of production thermally treated wood necessary to explore the distribution of moisture and temperature fields and heat treatment process to intensify the search for effective ways to prevent avoid possible ignition of wood that is exposed to thermal modification.